2016
DOI: 10.1111/jcpp.12657
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of cerebral surface morphology in youth with 22q11.2 deletion syndrome, and association with positive symptoms of psychosis

Abstract: Background 22q11.2 deletion syndrome (22q11DS) is a genetic disorder that greatly increases risk of developing schizophrenia. We previously characterized cerebral surface morphology trajectories from late childhood to mid adolescence in a cohort of youth with 22q11DS. Herein, we extend the study period into early adulthood, and describe further the trajectories associated with severe psychiatric symptoms in this cohort. Methods Participants included 76 youth with 22q11DS and 30 unaffected siblings, assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 71 publications
1
12
1
Order By: Relevance
“…Atypicalities in this regions have been linked to both ASD symptomatology 11 and prodromal symptoms of psychosis in 22q11.2DS 26 . In the occipital lobe, volumetric alterations have been linked to more pronounced symptoms of psychosis in both 22q11.2DS and the general population 27 , 28 . Our findings, and those of others, therefore highlight that some areas of the brain seem to be more affected than others in terms of their neuroanatomy in 22q11.2DS.…”
Section: Discussionmentioning
confidence: 99%
“…Atypicalities in this regions have been linked to both ASD symptomatology 11 and prodromal symptoms of psychosis in 22q11.2DS 26 . In the occipital lobe, volumetric alterations have been linked to more pronounced symptoms of psychosis in both 22q11.2DS and the general population 27 , 28 . Our findings, and those of others, therefore highlight that some areas of the brain seem to be more affected than others in terms of their neuroanatomy in 22q11.2DS.…”
Section: Discussionmentioning
confidence: 99%
“…The studies conducted to date showed alterations in cortical thickness, volume and gyrification in association to more severe positive symptoms (Schaer et al 2009; Gothelf et al 2011; Kates et al 2011; Jalbrzikowski et al 2013; Schmitt et al 2015; Bakker et al 2016), and reduced gyrification in association to higher negative symptoms (Mihailov et al 2017) in patients with 22q11DS. Furthermore, longitudinal investigations revealed altered developmental trajectories associated with higher positive symptoms severity in patients with the syndrome (Radoeva et al 2017; Ramanathan et al 2017). The regions more frequently associated to a more severe symptomatology included frontal and temporal cortices (Schaer et al 2009; Gothelf et al 2011; Kates et al 2011; Jalbrzikowski et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We decided not to include a control group of healthy subjects in order to avoid the influence of confounding factors, such as the important cognitive delay characterizing patients with 22q11DS. In addition, several studies already compared brain morphology measures between patients with 22q11DS and healthy controls (for instance Schmitt et al 2015; Bakker et al 2016; Radoeva et al 2017; Ramanathan et al 2017) and showed differences between the two groups even in patients with low psychotic symptoms scores. Therefore, we argue that the comparison of patients with 22q11DS meeting or not the UHR criteria will allow us to better define the brain phenotype associated to a greater risk of psychosis in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we found reduced thickness in frontal and fusiform/lingual cortices in patients with 22q11DS and schizophrenia compared to patients without psychosis ( Schaer et al, 2009 ). Furthermore, a recent study showed that impaired trajectories of cortical development in frontal and parietal regions were associated to increased severity of psychotic symptoms ( Radoeva et al, 2016 ). Gothelf et al further showed that white and grey matter volumes alterations in regions including the prefrontal cortex predicted the development of psychotic symptoms in patients with 22q11DS ( Gothelf et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%